HIV health information access using spoken dialogue systems: Touchtone vs. speech - Grover, A.S.; Plauche, M.; Barnard, E.; Kuun, C. (2009 International Conference on Information and Communication Technologies and Development, 2009)
This paper presents our work in the design of a SDS for the provision of health information to caregivers of HIV positive children. We specifically address the frequently debated question of input modality in speech systems; touchtone versus speech input, in a new context of low literacy users and a health information service. We discuss our experiences and fieldwork which includes needs assessment interviews, focus group sessions, and user studies in Botswana with semi and low-literate users. Our results indicate user preference for touchtone over speech input although both systems were comparable in performance based on objective metrics.